Cannabinoids and the Brain - Parker, Linda (Linda A.) (Book collections on Project MUSE., 2017)
The author presents a review of the scientific evidence on the effects of cannabinoids on brain and behavioral functioning, with an emphasis on potential therapeutic use. The author reviews the evidence on cannabinoids and anxiety, depression, mood, sleep, schizophrenia, learning and memory, addiction, sex, appetite and obesity, chemotherapy-induced nausea, epilepsy, and such neurodegenerative disorders as multiple sclerosis and Alzheimer's Disease. Each chapter of the text links the scientific evidence to historical and anecdotal reports of the medicinal use of cannabis.